CAMLG-CDG: a novel congenital disorder of glycosylation linked to defective membrane trafficking. Issue 15 (9th March 2022) - Wilson, Matthew P; Durin, Zoé; Unal, Özlem; Ng, Bobby G; Marrecau, Thomas; Keldermans, Liesbeth; Souche, Erika; Rymen, Daisy; Gündüz, Mehmet; Köse, Gülşen; Sturiale, Luisa; Garozzo, Domenico; et al.
Abstract: The transmembrane domain recognition complex (TRC) pathway is required for the insertion of C-terminal tail-anchored (TA) proteins into the lipid bilayer of specific intracellular organelles such as the endoplasmic reticulum (ER) membrane. In order to facilitate correct insertion, the recognition complex (consisting of BAG6, GET4 and UBL4A) must first bind to TA proteins and then to GET3 (TRC40, ASNA1), which chaperones the protein to the ER membrane. Subsequently, GET1 (WRB) and CAML form a receptor that enables integration of the TA protein within the lipid bilayer. We report an individual with the homozygous c.633 + 4A>G splice variant in CAMLG, encoding CAML. This variant leads to aberrant splicing and lack of functional protein in patient-derived fibroblasts. The patient displays a predominantly neurological phenotype with psychomotor disability, hypotonia, epilepsy and structural brain abnormalities. Biochemically, a combined O-linked and type II N-linked glycosylation defect was found. Mislocalization of syntaxin-5 in patient fibroblasts and in si CAMLG deleted Hela cells confirms this as a consistent cellular marker of TRC dysfunction. Interestingly, the level of the v-SNARE Bet1L is also drastically reduced in both of these models, indicating a fundamental role of the TRC complex in the assembly of Golgi SNARE complexes. It also points towards a possible mechanism behind the hyposialylation of N and O -glycans. This is the first reported patient with pathogenic variants in CAMLG . CAMLG-CDG is the third disorder, after GET4 and GET3 deficiencies, caused by pathogenic variants in a member of the TRC pathway, further expanding this novel group of disorders.